Notas sobre el español de Filipinas: documentos coloniales - Franco F., Mariano (Boletín de Filología, 2000)
We present documents referred to the colonial history of the Philippines (S. XVI-XVII), by various authors with diferent sociocultural levels, in order to emphasiee some of the linguistic aspects that characterize the Spanish language of these islands. The link between America and the Asian archipelago has been continuous during the Spanish dominion, for what it is no? strange to find linguistic similarities in their drferent speeches. The most evident conclusions allow us to consider that the language in the Philippines follows the changes that are produced in the New World, with a normalization of rules that emigrants use to produce a system that is more inclined to the meridional phonetic tendencies. A general repeated use of the /S/ sound is observed, as well as the graphic indifference of the sibilants, the absence of the f- replaced by h-, with evident signs of its aspiration, the confusion between /v/ and /b/, and neutralization of the liquid consonants and the omission of some implosive consonants like in the -S and -d endings. These linguistic habits settled in America do not hinder the language from acquiring the injluence of the geografic and cultural factors of the Philippines, specially in the native loan words.